(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2019)
Background: SSPE is a late complication of measles and is fatal in most cases. Objectives: The purpose of the study was to observe the clinico-demographic, investigation and outcome profiles of SSPE patients. Methodology: This prospective cohort study was conducted in the Department of Neurophysiology at National Institute of Neurosciences and Hospital, Dhaka, Bangladesh from September 2014 to August 2017. Patients of SSPE who were diagnosed by Dyken’s Criteria were selected as study population. Details socio-demographic, clinical profiles, investigations and outcome were recorded. The outcome was assessed from the time of first onset of the symptoms till closing of the study. Results: The mean age of the study population was 14.3±4.209 years with the male predominance (73.5%). Majority were from rural area (70.6%) and were of low socio-economic condition (52.9%). The mean age of onset of disease was 13.6±4.30 years. History of previous measles infection was reported in 13(38.2%) cases among which 12(92.3%) cases were vaccinated. The mean age of measles infection was 17.0±15.44 months. The time of first symptom of SSPE from primary measles infection was 11.50±4.80 years. Recurrent fall (47.1%) and myoclonic jerks (17.6%) were the most frequent initial symptoms of the patient. Cognitive decline was observed in 28(82.4%) cases. EEG background was slow in 23(67.6%) patients and periodic burst was observed in all (100.0%) cases. Anti-measles antibody in CSF was positive in all cases. MRI was abnormal in 7(25.9%) cases out of 27 cases. Twelve (35.3%) patients died, 18(52.9%) were alive and 4(11.8%) were lost to follow up when the study was closed. Conclusion: Early aged male from lower socioeconomic condition are found to be suffering from SSPE. Recurrent fall is the commonest initial presentation. Spontaneous recovery can occur in very few patients. Journal of National Institute of Neurosciences Bangladesh, 2019;5(2): 97-100